2000
DOI: 10.1038/sj.bjp.0703593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (+)‐pentazocine and 1,3‐di‐o‐tolylguanidine (DTG), sigma (σ) ligands, on micturition in anaesthetized rats

Abstract: 1 The e ects of two sigma (s) binding site ligands, (+)-pentazocine and 1,3-di-o-tolylguanidine (DTG), on bladder functions were examined in rats. 2 Cystometry using urethane-anaesthetized rats showed that (+)-pentazocine (1 ± 5 mg kg 71 , i.v.) and DTG (1 ± 5 mg kg 71 , i.v.) prolonged micturition intervals, indicating increased bladder capacity and raised the threshold pressure.3 The e ects of (+)-pentazocine (2 mg kg 71 , i.v.) on micturition were not in¯uenced by naloxone (0.5 mg kg 71 , i.v.), which antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…administration of naloxone also suggests that naloxone-induced changes in bladder compliance are unlikely to account for our results. Shimizu et al 30 also failed to find any influence of naloxone (0.5 mg/kg; i.v.) alone on various cystometric parameters and similar negative results have been reported in a conscious rat preparation.…”
Section: Discussionmentioning
confidence: 97%
“…administration of naloxone also suggests that naloxone-induced changes in bladder compliance are unlikely to account for our results. Shimizu et al 30 also failed to find any influence of naloxone (0.5 mg/kg; i.v.) alone on various cystometric parameters and similar negative results have been reported in a conscious rat preparation.…”
Section: Discussionmentioning
confidence: 97%
“…In the rat, MOR are known to be involved in central opioid modulation of bladder motility at both the supraspinal and spinal sites [20], [46], [47], [48]. In the rat spinal cord, both pharmacological and behavioral studies have provided compelling evidence that inhibition of micturition is mediated by MOR [31], [49], [50]. Bladder contractions may be inhibited by the MOR exogenous agonist morphine in an isovolumetric rat model, and this effect is abolished by the intravenous administration of the MOR antagonist naloxone [21], further suggesting that MOR in the spinal cord is involved in the regulation of bladder function.…”
Section: Discussionmentioning
confidence: 99%
“…Shimizu et al [2000Shimizu et al [ , 2001 showed that (þ)-pentazocine and 1,3-di-o-tolylguanidine (DTG) prolong micturition intervals, indicative of increased bladder capacity, and raised the threshold bladder pressure after either i.v. or i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…Dextromethorphan also exhibits relatively high a⁄nity for the sigma-1 receptor [Chou et al, 1999] and there is some evidence that sigma-1 receptors mediate its antitussive e⁄cacy [Brown et al, 2004]. Although relatively little is known about the role of sigma receptors in micturition, Shimizu et al [2000Shimizu et al [ , 2001 reported that sigma receptor agonists reduce the frequency of volume-induced bladder contractions, increase bladder capacity and raise the threshold pressure for micturition in anesthetized rats. Interestingly, the sigma receptor agonist 1,3-di-o-tolylguanidine also inhibits electrically stimulated contractions of isolated bladder strips in vitro [Shimizu et al, 2000].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation